UJI POTENSI TIGA VARIETAS JAGUNG DAN SAAT EMASKULASI TERHADAP PRODUKTIVITAS JAGUNG SEMI (BABY CORN) - Patola, Efrain -; Hardiatmi, Sri - (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2011)
Abstract The purpose of this research are (1) to known potency from three variety of corn to be developed as baby corn, (2) to known influence of the emasculation moment to baby corn productivity, and (3) to known influence of interaction between the emasculation moment and variety to baby corn productivity The research compiled factorially use Randomized Completely Block Design (RCBD) which consist of 2 factors and 3 replications. Factor 1 is variety by 3 levels, and factor 2 is the emasculation moment by 3 level. The result of the research, are: (1) variety of King Sweet and Chia Tai have potency to be developed as a baby corn variety, and require to be tested more continue, (2) the emasculation at time staminate emerge give influence better to number of cob without husk per plant, and (3) the interaction between variety with when emasculation non significant effect to all observation component. Key word : variety, emasculation, productivity, and baby corn